Deep-fried flavor: characteristics, formation mechanisms, and influencing factors - Chang, Chang; Wu, Gangcheng; Zhang, Hui; Jin, Qingzhe; Wang, Xingguo (Critical reviews in food science and nutrition, 2020)
Deep-fried flavor, involving fatty, sweet, burnt, and grilled odors, is an important factor leading to the popularity of deep-fried foods. Comparing with flavors from other conventional and innovative thermal treatments, deep-fried flavor is characterized by a rich variety of volatile species (e.g. aldehydes, alcohols, ketones, hydrocarbons, carboxylic acids, furans, pyrazines, and pyridines), intricate formation mechanisms, and a stronger attraction to consumers. By means of comprehensively literature research, this article critically reviews deep-fried flavor deriving from lipid oxidation, Maillard reaction, hydrolysis and amino acid degradation, with a special emphasis to discuss the involvement of lipid oxidation products in the Maillard pathway to form fried volatiles via secondary processes (e.g. fragmentation, rearrangement, and degradation). The reactions are interacted and influenced by various factors, such as frying oils (e.g. fatty acid composition and oil type), food components (e.g. amino acid and sugar), frying conditions (e.g. oxygen concentration, frying time, temperature, pH, and moisture content), and frying types (e.g. vacuum frying and air frying). Overall, well understanding of chemistry origins of deep-fried volatiles is meaningful to economically manipulate the frying process, optimize the fried flavor, and improve the safety and consumer acceptance of deep-fried foods.